2013
DOI: 10.3109/09593985.2012.757683
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity strength and range of motion and their relationship to function in breast cancer survivors

Abstract: The impact upper extremity impairments (UE) have on UE function in breast cancer survivors (BCS) is unclear. The purpose of this study was to evaluate the associations between upper extremity active range of motion (AROM), passive range of motion (PROM), and strength with self-reported function in BCS. BCS (n = 24) completed the Disabilities of Arm, Shoulder and Hand (DASH) and the Pennsylvania Shoulder Score (PSS). AROM and PROM of shoulder flexion, extension, external rotation (ER) at 0° and 90° of abduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 40 publications
(44 reference statements)
2
39
0
1
Order By: Relevance
“…At the end of the 4-week stretching treatment, an improvement in shoulder horizontal abduction was detected, but it did not lead to an improvement in upper-extremity symptoms, function, or quality of life. A previous study showed that the DASH score had the strongest correlation with shoulder range of motion, including rotation and abduction33 ) . However, no study has revealed a correlation between the presence of PMT and the DASH score.…”
Section: Discussionmentioning
confidence: 94%
“…At the end of the 4-week stretching treatment, an improvement in shoulder horizontal abduction was detected, but it did not lead to an improvement in upper-extremity symptoms, function, or quality of life. A previous study showed that the DASH score had the strongest correlation with shoulder range of motion, including rotation and abduction33 ) . However, no study has revealed a correlation between the presence of PMT and the DASH score.…”
Section: Discussionmentioning
confidence: 94%
“…Harrington et al studied the association of clinical measures of active and passive shoulder range of motion and strength with the scores from the DASH and from the pennsylvania shoulder scores (PENN) in 24 breast cancer patients. They reported a moderate to high correlation between active range of motion with the DASH, and strength with the PENN [15]. Although the study had strengths, it is limited by its small sample size and lack of assessment of other domains such as fatigue and pain.…”
Section: Upper Extremity Activities Of Daily Livingmentioning
confidence: 93%
“…Many authors rely on self-report using a variety of functional surveys, while other authors define function using clinical measurements of upper extremity range of motion and strength to indicate function [15,17,21,22,[39][40][41][42][43]. Lack of clinical measures to determine functional ability has been criticized [44]; however, there is little evidence in the literature that clinical measures of range of motion and strength can be used as a proxy for function.…”
Section: Upper Extremity Activities Of Daily Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests assessing scapula abduction and upward rotation, scapula depression and adduction, glenohumeral fl exion, internal rotation, scaption, and horizontal adduction strength as these were highly correlated with upper extremity functional loss in women diagnosed with breast cancer. 25 It is recommended that strength assessments be performed in a standardized manner such as published in Kendall et al 26 …”
Section: Breast Cancer-specific Objective Tests and Measuresmentioning
confidence: 99%